Building A Fuzzy Expert System For Flood Prevention - Leow, Meng Chew (2005)
The objective of this study is to find an alternative solution for flooding problem and to implement it. To do so, a detailed analysis of the current strategies dealing with flooding problem was first performed. Then, the causes and effects of a flood process were studied. From the detailed understanding , an alternative solution was proposed.